Evaluation Of Subjective Cognitive Function Using The Cognitive Complaints In Bipolar Disorder Rating Assessment (COBRA) In Japanese Adults - Toyoshima K (Dove Medical Press, 2019)
Kuniyoshi Toyoshima,1 Takeshi Inoue,2 Jiro Masuya,2 Masahiko Ichiki,2 Yota Fujimura,2 Ichiro Kusumi1 1Department of Psychiatry, Graduate School of Medicine, Hokkaido University, Sapporo, Japan; 2Department of Psychiatry, Tokyo Medical University, Tokyo, JapanCorrespondence: Kuniyoshi ToyoshimaDepartment of Psychiatry, Hokkaido University Graduate School of Medicine, Kita 15, Nishi 7, Sapporo 060-8638, JapanTel +81-11-716-1161Fax +81-11-706-5081Email toyoshima@med.hokudai.ac.jpPurpose: To examine the relationship between depressive symptoms, subjective cognitive function, and quality of life in Japanese adults using the Cognitive Complaints in Bipolar Disorder Rating Assessment (COBRA).Patients and methods: We evaluated 585 adult community volunteers using the Patient Health Questionnaire-9 (PHQ-9) for evaluation of depressive symptoms and the COBRA for evaluation of subjective cognitive function. We additionally used the 8-item Short-Form Health Survey and the Sheehan Disability Scale to evaluate the quality of life (QoL).Results: Measures of subjective cognitive function were significantly correlated with depressive symptoms and QoL. Structural equation modeling demonstrated that depressive symptoms directly and indirectly decreased QoL via their effects on subjective cognitive dysfunction. Measures of depressive symptoms were more closely related to QoL than were measures of subjective cognitive function.Limitations: Study participants were general adult population community volunteers and included healthy people; thus, these results may not be generalizable to patients with depression or bipolar disorder. In addition, the cross-sectional design of this study prevented the identification of causal relationships among the parameters.Conclusion: Changes in subjective cognitive function may affect QoL via depressive symptoms. Evaluations of subjective cognitive function may help identify factors that reduce QoL.Keywords: 8-item Short-Form Health Survey, Sheehan Disability Scale, Patient Health Questionnaire-9, QoL, subjective cognitive dysfunction